APLIKASI BAHASA C++ DAN PHP UNTUK MENENTUKAN UKURAN SAMPEL PADA METODE STRATIFIED RANDOM SAMPLING - Khanifudin khanifudin; Jajang Jajang; Bambang Hendriya Guswanto (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2020)
The accuracy of survey results depends on sample size. So far, in determining the sample size of the stratified random sampling method, researchers still use manual calculations. Because of that, this research aims to create a sample size determination program of the stratified random sampling method using C++ and PHP programming languages. This research begins with the study of literacy, creating flowcharts and pseudocode algorithms, writing program syntax, and implementing data on the number of civil servants in each UPK in Banyumas Regency. By entering a 95% confidence level, the error limit that can be tolerated is 5, and the strata cost of each is 1, the minimum sample size is 60 with the 1st and 2nd strata sample sizes is 45 and 15. The program is expected to help researchers to determine sample size more easily. So far, the program also minimizes errors in calculations because a warning will appear when an error occurs.